Hydraulic connections of leaves and fruit to the parent plant in Capsicum frutescens (hot pepper) during fruit ripening - Trifilò, Patrizia (Oxford University Press, 2010)
BACKGROUND AND AIMS: The hydraulic architecture and water relations of fruits and leaves of Capsicum frutescens were measured before and during the fruiting phase in order to estimate the eventual impact of xylem cavitation and embolism on the hydraulic isolation of fruits and leaves before maturation/abscission. METHODS: Measurements were performed at three different growth stages: (1) actively growing plants with some flowers before anthesis (GS1), (2) plants with about 50 % fully expanded leaves and immature fruits (GS2) and (3) plants with mature fruits and senescing basal leaves (GS3). Leaf conductance to water vapour as well as leaf and fruit water potential were measured. Hydraulic measurements were made using both the high-pressure flow meter (HPFM) and the vacuum chamber (VC) technique. KEY RESULTS: The hydraulic architecture of hot pepper plants during the fruiting phase was clearly addressed to favour water supply to growing fruits. Hydraulic measurements revealed that leaves of GS1 plants as well as leaves and fruit peduncles of GS2 plants were free from significant xylem embolism. Substantial increases in leaf petiole and fruit peduncle resistivity were recorded in GS3 plants irrespective of the hydraulic technique used. The higher fraction of resistivity measured using the VC technique compared with the HPFM technique was apparently due to conduit embolism. CONCLUSIONS: The present study is the first to look at the hydraulics of leaves and fruits during growth and maturation through direct, simultaneous measurements of water status and xylem efficiency of both plant regions at different hours of the day.